The hedgehog-poet: metric analysis of invective in the poetry of Archilochus (Circe de clásicos y modernos, 2020)
This article aims to investigate the poetic forms of Archilochus’ poetry in its relation with invective, from its metric aspect. In order to do that, after exposing the adopted metricological approach, -which is based on the notion of metric locations-, it seeks to highlight the inventiveness of the poet in the composition of metric structures that play with the audience expectations and reinforce the offensive sense of the compound verses. Finally, the author points out the relevance of metric analysis for the understanding of the poet’s compositions.
Keywords: iambic poetry; archaic Greek meter; Archilochus; Archilochus’ epodes; tetrameter trochaic